RESEARCH ON BUILDING AN ENVIRONMENTAL QUALITY MONITORING MANAGEMENT DEVICE USING THE INTERNET OF THINGS - Ho Thi Tuyen (Tạp chí Khoa học)
The paper proposes an innovative solution with a new air monitoring system that utilizes IoT technology, featuring compact, flexible, and automated nodes. This system operates without human intervention and can perform real-time measurements, reducing errors and consuming less energy. The product is developed and designed based on WiFi communication technology, NodeMCU Module, and the application of various sensors such as rain sensors, temperature-humidity sensors, soil moisture sensors, UV (Ultraviolet) sensors, dust sensors, fire sensors, and GAS sensors. The final product is a feasible hardware system for use in WiFi-covered areas, serving not only environmental monitoring but also households, farms, and agricultural areas.